Linking AKHLAK Culture to Engagement: The Mediating Role of Corporate Reputation - Sitanggang, Martua; Lubis, Rahmi; Turnip, Kaiman (Journal of Educational, Health and Community Psychology, 2025)
This study investigates the mediating role of corporate reputation in the relationship between the AKHLAK work culture and work engagement among 270 employees at PT X in Medan. Utilizing a quantitative approach and Structural Equation Modeling–Partial Least Squares (SEM-PLS) analysis, the results indicate that: (1) the AKHLAK culture significantly enhances work engagement (β = 0.494, p < 0.05); (2) the AKHLAK culture positively influences corporate reputation (β = 0.640, p < 0.05); (3) corporate reputation has a significant positive effect on work engagement (β = 0.328, p < 0.05); and (4) corporate reputation partially mediates the relationship between AKHLAK culture and work engagement (β = 0.210, p < 0.05). Theoretically, this study contributes to the expansion of the Job Demands–Resources (JD-R) Model and Social Identity Theory by positioning corporate reputation as a novel mediating variable. Practically, the findings emphasize the strategic importance of integrating AKHLAK values with corporate reputation-building efforts to enhance employee engagement and organizational competitiveness. These insights offer actionable guidance for Indonesian state-owned enterprises (SOEs) aiming to align cultural initiatives with broader reputational goals, thereby strengthening both internal morale and external stakeholder perception. Keywords: work culture AKHLAK, corporate reputation, work engagement